Magnetically Recoverable Catalysts: Beyond Magnetic Separation - Shifrina, Zinaida B.; Bronstein, Lyudmila M. (Frontiers in Chemistry, 2018)
Here, we discuss several important aspects of magnetically recoverable catalysts which can be realized when magnetic oxide nanoparticles are exposed to catalytic species and catalytic reaction media. In such conditions magnetic oxides can enhance performance of catalytic nanoparticles due to (i) electronic effects, (ii) catalyzing reactions which are beneficial for the final reaction outcome, or (iii) providing a capacity to dilute catalytic metal oxide species, leading to an increase of oxygen vacancies. However, this approach should be used when the magnetic oxides are stable in reaction conditions and do not promote side reactions. Incorporation of another active component, i.e., a graphene derivative, in the magnetically recoverable catalyst constitutes a smart design of a catalytic system due to synergy of its components, further enhancing catalytic properties.